The new intermediaries of tourist distribution: Analysis of online accommodation booking sites - Pablo de Carlos; Noelia Araújo; José Antonio Fraiz (The International Journal of Management Science and Information Technology (IJMSIT), 2016)
Distribution is a key variable in any industry because it ensures the delivery of products and services to consumers. However, over the years businesses have increasingly implemented information and communication technology; this has triggered profound changes in distribution channels. A number of tools have facilitated online access to information and booking for accommodations, flights or other travel products. This has substantially affected the traditional travel agency and tour operator business model. Moreover, new intermediaries have emerged. This paper aims to analyze the importance of current online and retail intermediaries operating in the distribution of tourism. To this end, it highlights metrics from a sample of 50 online accommodation booking portals with the greatest worldwide impact according to a classification published by SimilarWeb for the month of October 2014. In addition, it extensively analyzes the content of sites receiving over 10 million hits throughout this period.
Keywords: 650; distribution; tourism; online intermediaries; web analytics; content analysis; accommodation booking websites